Rumen methane output and fermentation characteristics of gramineous forage and leguminous forage at differing harvest dates determined using an in vitro gas production technique - Rong-zhen ZHONG; Yi FANG; Hai-xia SUN; Min WANG; Dao-wei ZHOU (Journal of Integrative Agriculture, 2016)
Abstract: An in vitro rumen gas production technique was employed to determine the methane production and fermentation characteristics of Leymus chinensis and Medicago ruthenica at differing harvest dates (May 15, May 30, June 30, July 30, August 30 and September 30), which are sequential phases within a single continuous growth of two 10-year-old pastures. To quantify the rate of degradation and compare in vitro rumen fermentation characteristic, a logistic-exponential model, where initial gas volume was zero (LE0), was used to fit gas production and methane output results. Dried, milled forage samples were incubated in vitro for 72 h at 39°C and gas production was recorded intermittently throughout the incubation and gas samples were collected to measure methane production. Results showed that there were significant interactions between species and harvest for all chemical composition variables (P<0.001) and condensed tannin content (P<0.001). L. chinensis produced more total gas and methane than M. ruthenica (P<0.001). Both total gas and methane production decreased lineally (P<0.001) with advancing harvest date. The degradation rates of L. chinensis and M. ruthenica harvested on September 30 were lower than those on the other harvest dates (P<0.01). M. ruthenica fermented fluid had higher concentration of ammonia N (P<0.05) and molar proportions of isobutyrate (P<0.01), valerate (P<0.001) and isovalerate (P<0.01) in total volatile fatty acids than L. chinensis. Furthermore, concentration of isovalerate decreased cubically with advancing harvest date (P<0.05). In conclusion, M. ruthenica produced less methane than L. chinensis and the total gas and methane production decreased with advancing harvest date for both species, which may be due to the changes in contents of chemical compositions and condensed tannin in forages.